Developing a microwave-driven reactor for ammonia synthesis: insights into the unique challenges of microwave catalysis. Issue 8 (29th March 2023) - Melkote, Sunjay G.; Muley, Pranjali; Dutta, Biswanath; Wildfire, Christina; Weiss, Robert; Hu, Jianli
Abstract : Reactor requirements grow with scale as new phenomena can become more and more relevant, creating trends that we've observed in the development of microwave-driven ammonia synthesis – a technique with a unique combination of high output and energy efficiency. Abstract : Rapid development of new ammonia (NH3 ) synthesis techniques that enable modular, intermittent production is essential to actualizing NH3 's potential as a clean energy carrier, since contemporary methods are configured to centralized, continuous production methods with high emissions and are incompatible with renewable sources. In this mission, microwave-driven catalysis is promising for its ability to enhance reaction kinetics and apply targeted heating for efficient energy use. However, owing to an incomplete understanding of the interaction between microwave fields and catalyst beds, the development of such microwave-catalysis systems remains underexplored and challenging. This paper investigates the 10× scale-up of a microwave-based NH3 synthesis reactor using numerical and experimental approaches, achieving the largest reported microwave-driven NH3 reactor to date. Results elucidate phenomena unique to microwave processes that are only predictable through numerical modeling, including how a catalyst's dielectric properties influence microwave field distribution by affecting penetration depth and how energy utilization can be poor even with sufficient attenuation. These dynamics change with scale, constrain reactor geometry, and potentially hamper performance. Nonetheless, we demonstrate a production rate of 56.6 gNH3 per day, the highest reported NH3 synthesis rate for laboratory-scale alternative techniques; correspondingly, the benchmark energy efficiency achieved in this paper (45.6 gNH3 kW h −1 ) is the highest reported for such reactors of sufficient scale. Even with this exemplary energy efficiency, energy losses were found in excess of 50%, an issue resolvable through scale and reactor design. The efficiencies imparted by microwaves were key in these achievements, warranting further investigation toward development of microwave-driven NH3 systems.